EXPLORING MOTIVATIONAL FACTORS BEHIND ALCOHOL CONSUMPTION: APPROACH TO TAILORED MARKETING - Kumar Goyal, Anil; Sufi, Tahir; Krishna Chaudhary, Hare (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2025)
This paper offers a comprehensive summary of the  debates and insights within the scientific discussion on the  motivations behind drinking cultures, specifically focusing  on factors driving alcohol consumption among millennials.  The primary objective of research is to identify the  motivational factors that encourage millennials to consume  alcoholic beverages. Systematization of existing literature  and approaches to addressing consumption trends among  millennials. The drinking habits are influenced by parental,  peer, societal pressures, emotional and psychological  needs. These patterns show that millennials turn to  alcohol as a coping mechanism for stress and failure, with  consumption frequently linked to socialization and stress  relief. The knowledge of these factors is critical to developing  effective marketing strategies for the millennial segment.   This research may help create effective and relevant  marketing strategies that connect with millennials’ reasons  for drinking. The paper, titled “Exploring Motivational  Factors Behind Alcohol Consumption: Approach to Tailored  Marketing” follows a structured and logical sequence to  present its findings.
Keywords: Alcoholic beverages; Dominance motives; External influences; Internal positive motive; Internal negative motives; Millennials